2019
DOI: 10.1111/1365-2435.13357
|View full text |Cite
|
Sign up to set email alerts
|

Foraging rates of ram‐filtering North Atlantic right whales

Abstract: North Atlantic right whales spend their summer months foraging primarily in American and Canadian Atlantic waters on high‐energy‐density prey. Here, they rapidly accumulate and store energy obtained within a few months to support future migrations and reproduction while fasting. High drag from their ram‐filter foraging strategy places a limit on what prey densities will be energetically efficient to target. Our understanding of the volume of prey‐laden water filtered by right whales during a dive or foraging b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 92 publications
(226 reference statements)
0
18
0
Order By: Relevance
“…From our meta‐analysis of data from 45 blue whales and 21 humpback whales that lunged multiple times per dive and for which georeferenced tracks could be calculated, we found that those two species traverse an average of 177 ± 51 and 73 ± 34 horizontal metres between lunges and average 4.1 ± 1.4 and 5.2 ± 2.3 lunges per dive, respectively, yet the distance travelled for one lunge is only the length of the buccal cavity (12.8 and 6.0 m, respectively, for a 22.5 m blue whale and 10.5 m humpback whale). Right whales, approximately the same length as humpback whales, are continuous ram filtration filters that filter an average of 670 m 3 of water on every dive (van der Hoop et al., 2019). At 14 m 3 of water engulfed per lunge (Kahane‐Rapport & Goldbogen, 2018), a humpback whale would have to lunge 48 times per dive (an order of magnitude more than their average) to filter an equivalent volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From our meta‐analysis of data from 45 blue whales and 21 humpback whales that lunged multiple times per dive and for which georeferenced tracks could be calculated, we found that those two species traverse an average of 177 ± 51 and 73 ± 34 horizontal metres between lunges and average 4.1 ± 1.4 and 5.2 ± 2.3 lunges per dive, respectively, yet the distance travelled for one lunge is only the length of the buccal cavity (12.8 and 6.0 m, respectively, for a 22.5 m blue whale and 10.5 m humpback whale). Right whales, approximately the same length as humpback whales, are continuous ram filtration filters that filter an average of 670 m 3 of water on every dive (van der Hoop et al., 2019). At 14 m 3 of water engulfed per lunge (Kahane‐Rapport & Goldbogen, 2018), a humpback whale would have to lunge 48 times per dive (an order of magnitude more than their average) to filter an equivalent volume.…”
Section: Discussionmentioning
confidence: 99%
“…Both the density of foraging predators and the types of collective behaviours displayed by groups are strongly driven across taxa by the heterogeneity, or patchiness, of resources in the environment (Gordon, 2014; Piatt & Methven, 1992), but effectively describing the availability of patchy resources to foragers is a fundamental challenge in ecology (Benoit‐Bird et al., 2013; Chave, 2013; Levin, 1992). Baleen whale (parvorder: Mysticeti) predator/prey systems are ideal for investigating the physiological drivers and ecological limits related to patchiness because, as capital‐breeding bulk filter‐feeders, baleen whales require dense concentrations of seasonally available prey; essentially, their life history is driven by both spatial (Hazen et al., 2009, 2015; van der Hoop et al., 2019; Piatt & Methven, 1992) and temporal patchiness (Abrahms et al., 2019; Fossette et al., 2017). Additionally, unusually in pelagic systems it is possible to study both the behaviour of baleen whales and the distribution of their euphausiid (krill) prey quantitatively and simultaneously in situ via the use of bio‐logging tags and hydroacoustic echosounders (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…First, are energetic costs more sensitive to lost feeding opportunities (reduced acquisition) or elevated locomotor effort (increased expenditure)? We hypothesize that lost feeding opportunities are more important because of the low cost of cetacean locomotion (Williams, 1999) and high foraging efficiency conferred by adaptations such as echolocation and bulk filter feeding (Goldbogen et al, 2017;van der Hoop et al, 2019;Watwood et al, 2006). Second, which species face the greatest immediate energetic costs relative to body size?…”
Section: Introductionmentioning
confidence: 99%
“…Copepods of the genus Calanus are the key components of zooplankton in the Arctic and northern Atlantic waters (Aarflot et al., 2017; Carstensen et al., 2019; Jaschnov, 1970), and they play a crucial role in marine food webs as the main mediators between the microbial system, phytoplankton, and higher trophic levels. Due to their high lipid content (Falk‐Petersen et al., 2009; van der Hoop et al., 2019; Mayzaud et al., 2016; Scott et al., 2000), they are responsible for the sustainability of large stocks of fish, seabirds, and marine mammals in the Arctic region (Falk‐Petersen et al., 2007, 2014; Stempniewicz et al., 2007). Additionally, due to the various centers of distribution of particular species, they are highly valued as biological indicators of the hydrographical–ecological regimes and consequently of the effects of ongoing climate changes (Choquet et al., 2017; Gabrielsen et al., 2012; Kwasniewski et al., 2010; Møller & Nielsen, 2019).…”
Section: Introductionmentioning
confidence: 99%